Network Structure of Japanese Firms Hierarchy and Degree Correlation: Analysis from 800,000 Firms - Tomohiko Konno (Kiel Institute for the World Economy (IfW), 2008)
We found hierarchical structure and negative degree correlation in firms' transaction network. The network consists of 800,000 Japanese firms. We also summarize other features of the network and discuss why studying network structure is important. We also found scale free distribution in undirected network.
Keywords: L16; 330; Network of firms; scale free network; complex network; hierarchy; degree correlation; Business Network; Lieferanten-Kunden-Beziehung; Wirtschaftskonzentration; Japan